Cyanobacterial Diversity in Selected Tor tambroides Cultivation Areas in Serian and Satang Ai, Sarawak - Harith, Mohd Nasarudin; Hassan, Ruhana (2012)
This study aims to assess cyanobacterial diversity in three types of Tor tambroides cultivation areas namely HOPE (High Density Polyethylene) layered ponds, earth ponds and cage culture in Serian and Batang Ai, Sarawak. The Sorensen's Quotient of Similarity (SQS) values were calculated and analyzed to determine the similarity in genera composition between stations. From 25 cyanobacteria genera recorded in all stations, 40% were categorized as potential toxin producers. The wide range of SQS value suggested that different types and location of ponds will have variation in physico-chemical properties of the water and lead to the different composition of cyanobacteria. Toxic cyanobacteria for example genera Micro cystis , Anabaena and Oscillatoria may present risk of cyanotoxin bioaccumulation in fish tissues and posed hazards to aquatic animals and humans. Therefore, this research is essential in establishing baseline data on the freshwater cyanobacterial species that exist in different types of Tor tambroides cultivation areas. The data will be useful in risk assessment of the potential cyanotoxin contamination in water and bioaccumulation in Tor tambroides.